The Influence of Lateral Restraining Stiffness on the Box-Girder Superstructure under Unbroken Solitary Waves - Minglin Chen; Bo Huang; Zhiying Yang; Qingyang Ren; Bing Zhu (Journal of Marine Science and Engineering, 2022)
At present, box-girder superstructures are commonly used in coastal bridges, and their hydrodynamic performance under extreme waves such as tsunamis has attracted a lot of attention. There is a lack of research focusing on the effect of lateral restraining stiffness on box-girder superstructures under the extreme wave condition. In this paper, a two-dimensional numerical model based on the RANS equation and SST k-ω turbulence model is established. Combined with the dynamic mesh updating technique, the effect of lateral restraining stiffness on the superstructure of a box-girder and the dynamic characteristics of the movable box-girder under the solitary waves were investigated. To ensure the mesh quality, the numerical computational domain is divided into several regions that correspond to specific types of body motion. The numerical model is verified by comparing it with other numerical simulation results and experimental results. The dynamic characteristics and the wave forces of the box-girder superstructure under the effect of lateral restraining stiffness under the unbroken solitary waves are discussed. The results show that the horizontal and vertical forces on the box-girder superstructure under the action of unbroken solitary waves can be reduced by reducing the lateral restraining stiffness. However, with the decrease in lateral restraining stiffness, the lateral displacement of the box-girder superstructure would increase. Therefore, the lateral restraining stiffness and lateral displacement limit of the box-girder superstructure should be fully considered in practical engineering, and the appropriate lateral restraining stiffness should be selected to reduce the wave forces on the box-girder superstructure under extreme wave action, so as to improve the safety of the coastal box-girder superstructure. It is of great importance to study the interaction between the box-girder superstructure and unbroken solitary waves, which will help to have a deeper understanding to improve the disaster resistance of bridges.